Decision Making For Recruitment and Promotion Policies Using Linear Programming - Bilkisu Maijamaa; Otinya Gabriel (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2022)
Optimizing decision is one of the procedures used for maximization of benefit with minimization of cost. To achieve a meaningful development in any organization, proper allocation of funds is needed with minimized cost. There would be no meaningful development in any organization that will not involve recruitment and promotion. The method used in this study for optimizing a manpower recruitment and promotion is linear programming approach, proposing a model and applying the model on data collected from hypothetical data for optimizing recruitment and promotion for N-grade manpower system. The output from the research was able to identify the total costs of recruitment is 17,433,800 (seventeen million, four hundred and thirty-three thousands, eight hundred naira) with 22 (twenty-two recruited staff. The total costs for promotion is 10,297,800 (ten million, two hundred and ninety-seven thousands, eight hundred naira) with 22 (twenty-two) staff promoted. From the model formulated, it can be applied by other organization considering recruitment and promotions of staff with a minimized cost for the manpower system when faced with limited available resources.